Stress and hypertension: A thorough investigation into how engineering college students at Tobruk University - Abdelmola هناء جمعة علي (Sebha University Conference Proceedings, 2025)
Introduction: Academic stress among university students may contribute to hormonal dysregulation and hypertension, yet its impact remains understudied in Libya. Materials and Methods: This study assessed hormonal changes in 32 Pharmacy College students (18 males, 14 females, aged 18–25) at Tobruk University using the Snibe Diagnostic MASRADAR X3. Blood samples were collected one week before and after final examinations to measure Growth Hormone (GH), Histamine, Adiponectin, Angiotensin I, Cortisol Binding Globulin (CBG), Creatine Kinase (CK), Glucagon, and Angiotensin II. Paired t-tests were used for analysis (p < 0.05). Results: Significant reductions were observed post-examination in GH (8.69 to 5.03 ng/mL), CBG (57.16 to 37.06 µg/mL), CK (180.97 to 83.03 U/L), Glucagon (233.58 to 70.52 pg/mL), and Angiotensin II (70.32 to 37.29 pg/mL). Histamine increased (4.62 to 6.31 ng/mL). Adiponectin and Angiotensin I showed no significant changes. Blood pressure increased during exams, with 36.7% of Organic Chemistry students showing hypertension (≥130/85 mmHg). Conclusion: Examination stress significantly alters hormonal profiles, potentially increasing hypertension risk. Stress management programs are recommended to mitigate these effects.